Method for preparing microporous polyether-ether-ketone biological material through 3D metal printing

Microporous polyether etherketone biomaterials were prepared through 3D metal printing technology, and modified by sulfonation and wet chemical methods, solving the shortcomings of existing skull repair materials in mechanical and biological reactions, achieving high biocompatibility of the materials and mechanical properties promote the growth of new bone tissue.

CN119463284AInactive Publication Date: 2025-02-18CHENGDU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510040176.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing skull repair materials have mechanical limitations and negative biological responses in vivo, and traditional preparation methods have shortcomings in pore size accuracy, pore uniformity, spatial structure complexity and personalized control.

Method used

Microporous polyether etherketone biomaterials are prepared by 3D metal printing technology. Modification by sulfonation reaction and wet chemical method can increase the biological activity and mechanical properties of the material and form a bone coating and continuous microporous structure.

Benefits of technology

It improves the biocompatibility and bone integration ability of the material, reduces the "stress shielding" effect, enhances the mechanical properties and biological activity of the material, and provides a good environment to promote the growth of new bone tissue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463284A_ABST
    Figure CN119463284A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a microporous polyether-ether-ketone biological material through 3D metal printing, and belongs to the technical field of medical materials. Comprising the following steps that 3D Max software is adopted, models are designed, model files are exported in the. STL format, Ultimaker Cura software is imported to adjust parameters, slicing operation is conducted, the filling rate and the theoretical porosity are set, and a first slicing model is stored in the. GCODE format and exported for standby application; the stored. GCODE file is imported into a 3D printer, and a polyether-ether-ketone support is printed; cleaning and drying the printed polyether-ether-ketone bracket to obtain unmodified polyether-ether-ketone; carrying out sulfonation reaction on the surface of the unmodified polyether-ether-ketone by using concentrated sulfuric acid; forming a bioactive apatite layer on the substrate; and modifying by a wet chemical method, and drying to obtain the sulfonated polyether ether ketone-apatite. The stability of the implant is improved; the polyether-ether-ketone has good biocompatibility, and the nano-hydroxyapatite has good biocompatibility and excellent osteogenic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a method for preparing microporous polyetheretherketone biomaterial by 3D metal printing, belonging to the technical field of medical materials. Background Art

[0002] At present, the research on skull repair includes materials such as titanium alloy, polyetheretherketone, skull tissue engineering and 3D printing technology. Titanium alloy is a widely used skull repair material in clinical practice. It has low density and high strength. Therefore, titanium alloy has high specific strength. Patients will not feel heavy after the titanium alloy is implanted. In addition, it has good tissue compatibility, good stability, low sensitization, and less interference with CT and MRI examinations. These characteristics are also the reasons why titanium alloy materials are used as skull repair materials. However, the release of harmful metal ions in the body and the radiation blocking of metal materials have attracted people's attention. In addition, the elastic modulus of titanium and titanium alloys (102~110GPa) is dozens of times that of cortical bone (14GPa). This huge difference will produce stress shielding, leading to bone resorption and affecting the long-term success rate of surgery. In order to overcome mechanical limitations and minimize negative biological reactions after implantation, people began to seek alternative materials to titanium.

[0003] At the same time, the traditional method of preparing skull repair scaffolds has poor controllability in terms of pore size accuracy, pore uniformity, spatial structure complexity, scaffold personalization, etc., which is not conducive to the growth of bone tissue. Summary of the invention

[0004] The present invention is based on how to avoid complications such as loosening and failure of skull repair materials and develop new skull repair biomaterials, and studies the issues of how to improve the surface biological activity of the new skull repair biomaterial polyetheretherketone, improve bone integration ability, improve surface morphology, prepare osteogenic coatings and continuous microporous structures while maintaining good mechanical properties. It is expected that the preparation method of the present invention can produce a microporous polyetheretherketone / nanohydroxyapatite biomaterial with osteogenic coatings and continuous microporous structures while maintaining good mechanical properties.

[0005] The specific technical solution of the present invention is: The method for preparing microporous polyetheretherketone biomaterial by 3D metal printing comprises the following steps: (1) Using 3D Max software, the model was designed as a 10×10×10 mm cube and a 20×20×1.5 mm slice. The model file was exported in .STL format and then imported into Ultimaker Cura software to adjust the parameters and perform slicing operations. The filling rate was set to 30% and the theoretical porosity was set to 70%. The sliced ​​model was saved in .GCODE format and exported for later use.

[0006] (2) Import the saved .GCODE file into the 3D printer to print the PEEK scaffold. Import the sliced ​​.GCODE file into the 3D printer. Preheat the fused deposition model (FDM) 3D printer base to 100°C, set the printing pressure to adapt, set the nozzle aperture to 0.4 mm, the material diameter to 1.75 mm, the layer height to 0.2 mm, the wall thickness to 1 mm, and the printing speed to 20 mm / s. Then insert the PEEK biomedical-grade printing filament into the printing conveyor tube. After the base is heated to 100°C and the print head temperature is heated to 400°C, select the preset model file and start printing. The printed PEEK scaffold is ultrasonically washed with acetone, ethanol, and deionized water for 15 min in turn, placed in an oven at 37°C for drying, and then placed in a clean beaker to obtain unmodified PEEK.

[0007] (3) Concentrated sulfuric acid (98%) was injected into a beaker to completely immerse the surface of polyetheretherketone, and the sulfonation reaction was carried out at 37°C and 250 r / min with sufficient stirring. After 3 minutes, the sample was taken out, rinsed three times with deionized water, and then ultrasonically cleaned in acetone, ethanol and ultrapure water for 10 minutes to remove the residue. The sample was freeze-dried in a vacuum freeze dryer. Then, the sample was soaked in deionized water for 5 minutes, rinsed repeatedly with deionized water, and then ultrasonically cleaned in acetone, ethanol and ultrapure water for 10 minutes to remove the residue. The sample was freeze-dried in a vacuum freeze dryer to obtain sulfonated polyetheretherketone.

[0008] (4) The sulfonated sample was immersed in simulated body fluid (SBF) to form a bioactive apatite layer on the substrate.

[0009] (5) Under the conditions of pH = 7.4 and temperature of 37-70°C, after 1-3 days, the samples were taken out and placed in an oven at 37°C for drying to obtain sulfonated polyetheretherketone-apatite.

[0010] The technical effects of the technical solution of the present invention are as follows: 1. The present invention adopts 3D metal printing technology to prepare microporous polyetheretherketone biomaterials, which overcomes the problem of organic solvent residues in traditional preparation methods. And adding microporous structures to polyetheretherketone through this method can promote the growth of new bone tissue in the microporous structure, thereby providing a good environment for the growth of new bone, thereby forming more biological anchors with the host bone, thereby improving the stability of the implant, which is a new strategy to promote osteogenesis and binding with the host bone.

[0011] 2. Polyetheretherketone has good biocompatibility, mechanical strength and elastic modulus similar to that of human bones. As an implant material, it will effectively reduce the "stress shielding" effect. Nanohydroxyapatite has good biocompatibility and excellent osteogenic activity. Previous studies have confirmed that it has good osteoconductivity and good osteogenic ability in the body. The present invention combines the excellent biomechanical properties of polyetheretherketone with the excellent biological activity of nanohydroxyapatite to prepare a biomaterial with a microporous structure, providing new ideas and methods for the development of new skull repair biomaterials with excellent biomechanical properties and excellent biological activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a macroscopic morphology of an unmodified polyetheretherketone scaffold printed by the fused deposition 3D printing technology of an embodiment; Figure 2 This is a macroscopic morphology of the polyetheretherketone stent treated by sulfonation in the embodiment; Figure 3 This is a macroscopic morphology of the polyetheretherketone stent modified by wet chemical method in the embodiment; Figure 4 This is one of the microscopic morphology images of the unmodified polyetheretherketone stent of the embodiment; Figure 5 This is the second microscopic morphology image of the unmodified polyetheretherketone stent of the embodiment; Figure 6 This is the third microscopic morphology image of the unmodified polyetheretherketone stent of the embodiment; Figure 7 This is one of the microscopic morphology images of the sulfonated polyetheretherketone stent in the embodiment; Figure 8 This is the second microscopic morphology image of the sulfonated polyetheretherketone stent of the embodiment; Fig. 9 This is the third microscopic morphology image of the sulfonated polyetheretherketone stent of the embodiment; Fig.10 This is one of the microscopic morphology images of the sulfonated polyetheretherketone-apatite scaffold of the embodiment; Fig.11 This is the second microscopic morphology image of the sulfonated polyetheretherketone-apatite scaffold of the embodiment; Fig.12 The third microscopic morphology image of the sulfonated polyetheretherketone-apatite scaffold of the embodiment; Fig.13 This is an EDS analysis diagram of the 5X-70C-72H sulfonated polyetheretherketone-apatite group stent in the embodiment; Fig.14 The infrared spectrum analysis diagrams of the three groups of brackets of unmodified polyetheretherketone, sulfonated polyetheretherketone, and sulfonated polyetheretherketone-apatite in the embodiment; Fig.15is a thermogravimetric curve of the unmodified polyetheretherketone stent of the embodiment; Fig.16 This is an atomic force microscope analysis image of the unmodified polyetheretherketone of the embodiment; Fig.17 This is an atomic force microscope analysis image of the sulfonated polyetheretherketone of the embodiment; Fig.18 This is an atomic force microscope analysis image of sulfonated polyetheretherketone-apatite of the embodiment; Fig.19 Surface roughness analysis diagrams of three groups of polyetheretherketone stents, namely, unmodified polyetheretherketone, sulfonated polyetheretherketone, and sulfonated polyetheretherketone-apatite, in the embodiments; Fig. 20 Root mean square roughness analysis diagram of three groups of polyetheretherketone stents, namely, unmodified polyetheretherketone, sulfonated polyetheretherketone, and sulfonated polyetheretherketone-apatite, in the embodiment; Fig.21 This is a contact angle measurement diagram of the unmodified polyetheretherketone stent surface of the embodiment; Fig. 22 This is a contact angle measurement diagram of the sulfonated polyetheretherketone stent surface in the embodiment; Fig.23 This is a contact angle measurement diagram of the sulfonated polyetheretherketone-apatite stent surface in the embodiment; Fig.24 It is a hydrophilicity analysis diagram of different scaffolds of the embodiment; Fig.25 The compression modulus and compressive strength diagram of the stent of the embodiment; Fig.26 is a diagram of the compressive strength of the bracket of the embodiment; Fig. 27 This is a first picture of the cell morphology observation of BMSCs cultured on the unmodified polyetheretherketone scaffold on the 7th day in the example; Fig.28 This is the second picture of the cell morphology observation of BMSCs cultured on the unmodified polyetheretherketone scaffold on the 7th day of the example; Fig.29 This is a first picture of cell morphology observation of BMSCs cultured on sulfonated polyetheretherketone scaffolds on day 7 in the example; Fig.30 Figure 2 is the cell morphology observation of BMSCs cultured on the sulfonated polyetheretherketone scaffold on the 7th day in the example; Fig.31 This is a first picture of cell morphology observation of BMSCs cultured on sulfonated polyetheretherketone-apatite scaffold on day 7 in the example; Fig.32 Figure 2 of the cell morphology observation of BMSCs cultured on the sulfonated polyetheretherketone-apatite scaffold on the 7th day in the example; Fig.33 OD values ​​of polyetheretherketone stents with different coatings at 1, 3, and 5 days in the embodiment; Fig.34 The cell activity diagrams of polyetheretherketone scaffolds with different coatings at 1, 3, and 5 days in the embodiment; Fig.35 ALP activity graph of BMSCs cells at 7 and 14 days in the embodiment; Fig.36 The staining images of unmodified polyetheretherketone scaffolds with different coatings in the embodiment after 7 days of osteogenic induction; Fig.37 The staining images of unmodified polyetheretherketone scaffolds with different coatings in the embodiment after 14 days of osteogenic induction; Fig.38 This is a staining image of the sulfonated polyetheretherketone scaffolds with different coatings in the embodiment after 7 days of osteogenic induction; Fig.39 The staining images of the sulfonated polyetheretherketone scaffolds with different coatings in the embodiment after 14 days of osteogenic induction; Fig.40 The staining images of sulfonated polyetheretherketone-apatite scaffolds with different coatings after 7 days of osteogenic induction in the embodiment; Fig.41 The staining images of sulfonated polyetheretherketone-apatite scaffolds with different coatings after 14 days of osteogenic induction are shown in the examples. DETAILED DESCRIPTION

[0013] The specific technical solution of the present invention is explained in conjunction with embodiments.

[0014] This embodiment uses patient head specimens as the research object. First, head CT scan data is obtained by high-resolution spiral CT scanning. Secondly, the DICOM format image data obtained by scanning is imported into the medical image data processing software Materialise Mimics21.0, and the patient's skull mask is generated by threshold segmentation, and the edge of the mask is manually edited on the cross section, and point cloud data is generated by smoothing. Thirdly, the point cloud data processed by Mimics is imported into the engineering design software UG12.0 for reverse processing to establish a skull model. Finally, the skull model is converted into STL format and imported into the PrusaSlicer software for slicing and printing parameter setting, and the FDM 3D printer is used for 1:1 printing.

[0015] This example tests and evaluates the physicochemical properties, mechanical properties and related characterization of microporous polyetheretherketone / nanohydroxyapatite biomaterials. Through relevant experiments, the effects of biomaterials on the biosafety, cytocompatibility and biological activity of MC3T3-E1 osteoblasts were systematically evaluated, and further preliminary evaluation studies were conducted on its biosafety, in vivo vascularization, osteogenesis and bone integration capabilities through animal in vivo skull defect repair experiments.

[0016] 1. Preparation and characterization analysis of 3D printed polyetheretherketone scaffolds 1.1 Preparation of polyetheretherketone scaffold 3D Max (Discreet, Canada) was used to design the model of a 10×10×10 mm cube and a 20×20×1.5 mm slice. The model file was exported in .STL format and then imported into Ultimaker Cura (Ultimaker, Netherlands) to adjust the parameters and perform slicing operations. The filling rate was set to 30%, and the theoretical porosity was corresponding to 70%. The sliced ​​model was saved in .GCODE format and exported for later use.

[0017] Import the saved .GCODE file into the 3D printer to print the polyetheretherketone scaffold. Import the sliced ​​.GCODE file into the 3D printer. Preheat the fused deposition model (FDM) 3D printer base to 100°C, adapt the printing pressure, set the nozzle aperture to 0.4 mm, the material diameter to 1.75 mm, the layer height to 0.2 mm, the wall thickness to 1 mm, and the printing speed to 20 mm / s. Then insert the polyetheretherketone biomedical-grade printing filament into the printing conveyor tube. After the base is heated to 100°C and the print head temperature is heated to 400°C, select the preset model file and start printing. The printed polyetheretherketone scaffold was ultrasonically washed with acetone, ethanol, and deionized water for 15 min in turn, placed in an oven at 37°C for drying, and then placed in a clean beaker as the unmodified polyetheretherketone group.

[0018] Concentrated sulfuric acid (98%) was injected into a beaker to completely immerse the surface of polyetheretherketone, and the sulfonation reaction was carried out at 37℃ and 250 r / min with full stirring. Take it out after 3 minutes, rinse it repeatedly with deionized water three times, and then ultrasonically clean it in acetone, ethanol and ultrapure water for 10 minutes to remove the residue. And freeze-dried it in a vacuum freeze dryer. Then, soak the sample in deionized water for 5 minutes, rinse the sample repeatedly with deionized water, and then ultrasonically clean it in acetone, ethanol and ultrapure water for 10 minutes to remove the residue. And freeze-dried it in a vacuum freeze dryer as a polyetheretherketone group.

[0019] The sulfonated samples were immersed in simulated body fluid (SBF) 5X SBF and 10X SBF to form a bioactive apatite layer on the substrate. Under the conditions of pH = 7.4, temperature 37°C and 70°C (as shown in Table 1), the samples were taken out on the first day and the third day, respectively, and placed in an oven at 37°C for drying, which was recorded as the sulfonated polyetheretherketone-apatite group. At the same time, the sulfonated polyetheretherketone-apatite group was recorded as 1X-37C-24H, 1X-37C-72H, 1X-70C-24H, 1X-70C-72H, 5X-37C-24H, 5X-37C-72H, 5X-70C-24H, and 5X-70C-72H according to different time and temperature.

[0020] Table 1 Wet chemical coating conditions

[0021]

[0022] 1.2 Surface morphology analysis A high-definition camera was used to capture the appearance and morphology of three groups of polyetheretherketone scaffolds prepared by 3D printing fused deposition technology, and their macroscopic morphology was observed.

[0023] 1.3 Microscopic morphology and structure observation Place three groups of polyetheretherketone brackets on the operating table, spray gold on the three groups of prepared samples, place the samples in a scanning electron microscope, adjust the parameters, current 10μA, acceleration voltage 10 KV. Use a scanning electron microscope (SEM) to observe the microscopic morphology of the three groups of polyetheretherketone brackets. Observe the surface morphology of the samples and take microscopic morphology pictures according to different magnifications.

[0024] 1.4 Element distribution analysis The distribution of surface elements of the three groups of polyetheretherketone stents was analyzed using an EDS spectrometer (EDS, JSM-6490LV), and the proportion of surface material components of the sulfonated polyetheretherketone-apatite group modified by sulfonation + wet chemical method was quantitatively analyzed. The operation steps are as follows: first, the three groups of polyetheretherketone stent samples were placed on the operating table using conductive glue, and after gold spraying, the acceleration voltage was set to 5 kV, and the types of elements on the surface of the three groups of polyetheretherketone stents were analyzed.

[0025] 1.5 Fourier transform infrared spectroscopy The infrared characteristic absorption peaks of the three groups of polyetheretherketone brackets were analyzed. First, the background wave was collected according to the operation process, and then the three groups of polyetheretherketone brackets were placed on the infrared spectrometer workbench and the infrared absorption peaks were measured at 1800~400 cm -1 The experimental data were recorded within the wavelength range, and the data were collected after the scanning was completed. The infrared characteristic absorption peak data of the three groups of polyetheretherketone scaffolds were processed and analyzed by Origin drawing software.

[0026] 1.6 Thermogravimetric analysis After drying, the three groups of polyetheretherketone stents were placed in a thermogravimetric analyzer, using nitrogen as the carrier gas and setting the parameters to a flow rate of 100 cm 3 / min, the temperature range is 20-600°C, the temperature increases at a rate of 10°C / min, and the thermal properties of the three groups of polyetheretherketone scaffolds are analyzed using a thermogravimetric analyzer (TGA, TA2050).

[0027] 1.7 Hydrophilicity analysis The hydrophilicity of three groups of polyetheretherketone scaffolds was detected by the liquid static drop method. At room temperature of 24°C, the experimental samples were placed on the operating test bench, and then 5 μL of deionized water was dropped onto the surface of the scaffold. After standing for 20 seconds, a water contact angle meter (JC, 2000D3) was used to take pictures and measure the water contact angle. Three samples were measured in each group, and three different points were measured for each sample. Finally, the average value was calculated, and statistical analysis was performed, and the graph was drawn using GraphPad Prism software.

[0028] 1.8 Porosity analysis The Archimedes drainage method was used to test the PEEK stents with different coatings. The medium used in this experiment was anhydrous ethanol. First, the length, width and height of the PEEK stent were measured with a vernier caliper, and the apparent volume of the PEEK stent was calculated, recorded as V. a . Then measure and record the initial liquid level of anhydrous ethanol in the test tube, and then immerse the polyetheretherketone bracket (10×10×10 mm) in the test tube so that the polyetheretherketone bracket is completely immersed in anhydrous ethanol. Tap the test tube lightly to allow anhydrous ethanol to fully enter the pores of the polyetheretherketone bracket. After standing for 24 hours and no more bubbles overflowing from the test tube, measure the height of anhydrous ethanol in the test tube and calculate the volume of the liquid surface rise, which is recorded as V b . Three parallel samples were set for each group. The final porosity calculation formula is as follows: , Among them, ε is the porosity. Finally, the experimental data were recorded, and the pore size analysis was performed on the SEM images of the polyetheretherketone scaffolds with different coatings using Nano measurer (Nano measurer, USA) software, and the output results were input into GraphPad Prism software for statistical analysis.

[0029] 1.9 Atomic Force Microscopy (AFM) The surface roughness of the three groups of tissue artificial bones was characterized by atomic force microscopy. First, the three groups of tissue artificial bones were placed on the sample stage, and then the sample stage was placed on the atomic force microscope observation platform. The parameters were set, the scanning range was 100 μm, the scanning voltage was 20 V, and the scanning height was 1000 nm. The probe fluctuation curve was observed in real time, and the scanning height was adjusted in real time. After the scanning was completed, the surface morphology and roughness data of the experimental samples were obtained. Then the experimental data were imported into Gwyddion software for three-dimensional image processing. The surface roughness of polyetheretherketone scaffolds with different coatings was exported in Gwyddion software and imported into GraphPad Prism software for drawing and statistical analysis.

[0030] 1.10 Mechanical properties analysis The mechanical properties of the three groups of polyetheretherketone scaffolds were tested by a universal testing machine (Instron 5967) to evaluate the compressive strength of the three groups of scaffolds. The compression modulus and compressive strength of the three groups of polyetheretherketone scaffold samples were tested according to the national standard GB / T1040.1-2018. Five parallel samples were selected from each group of polyetheretherketone scaffolds and placed in the compression module of the universal mechanical testing machine. The parameters were set as follows: the moving speed of the force head was 2 mm / min, the sensor was 20 kN, and the output results of the instrument were imported into the GraphPad Prism software for drawing, calculating the mean and standard deviation, and completing statistical analysis.

[0031] 2 In vitro cell experiments on modified polyetheretherketone 2.1 Cell culture and material preparation Prepare 5*5*1mm scaffolds of polyetheretherketone, sulfonated polyetheretherketone, and sulfonated polyetheretherketone-apatite groups, dry them in a vacuum oven for 12 h, and sterilize the samples with ultraviolet sterilization for 24 h. Prepare complete medium for rat bone marrow mesenchymal stem cells (basal medium 440 mL, fetal bovine serum 50 mL, double antibody 5 mL, glutamine 5 mL) and osteogenic induction medium for rat bone marrow mesenchymal stem cells (basal medium 175 mL, fetal bovine serum 20 mL, double antibody 2 mL, glutamine 2 mL, ascorbic acid 400 μL, sodium β-glycerophosphate 2 mL, dexamethasone 20 μL) for use. Resuspend and resuscitate rat bone marrow mesenchymal stem cells, place them in complete medium, subculture them to the third generation of cells, and store them for use.

[0032] 2.2 Cell morphology observation Add 2 ml of complete medium of rat bone marrow mesenchymal stem cells to a 24-well plate, sterilize the prepared scaffold with high-temperature and high-pressure steam, and fix it on the plate. Implant the prepared rat bone marrow mesenchymal stem cells at a concentration of 3×10 5 cm-2 , placed in a constant temperature incubator at 37°C for culture. After 7 days, the culture plate was taken out and centrifuged at 1000 rpm / min for 1 minute. The liquid in the wells was aspirated, and the cells were gently rinsed with PBS. They were fixed with 4% paraformaldehyde for 24 hours. After ethanol dehydration and drying and gold spraying, the samples were observed using a scanning electron microscope.

[0033] .2.3 Preparation of artificial extracts for tissue engineering The three groups of materials were sterilized with a hydrogen peroxide low-temperature plasma sterilizer, and artificial bone extracts were prepared according to the national medical device evaluation method. The three groups of materials, polyetheretherketone, sulfonated polyetheretherketone, and sulfonated polyetheretherketone-apatite, were placed in complete culture medium and placed in a constant temperature cell culture incubator for 72 hours to obtain complete culture medium extracts of the three groups of materials and stored at 4°C for cell proliferation experiments. According to the above preparation standards and methods, the three groups of materials were placed in rat bone marrow mesenchymal stem cell osteogenic induction culture medium for extraction, and the three groups of materials osteogenic induction culture medium extracts were prepared for cell mineralization experiments.

[0034] 2.4 Cell proliferation and cytotoxicity analysis The cell compatibility of bone marrow mesenchymal stem cells on three groups of polyetheretherketone scaffold samples was determined by CCK-8 cell proliferation assay. 50 μL of cell suspension containing BMSCs (6×10 5 / mL), and then 100μL complete culture medium was dropped into each well and cultured in a constant temperature incubator. After 24 hours, the well plate was taken out to replace the culture medium, and the three groups of extracts prepared in advance were added to the culture medium. According to the different extracts added, the three groups were set as polyetheretherketone group, sulfonated polyetheretherketone group, and sulfonated polyetheretherketone-apatite group, respectively. At the same time, the complete culture medium group containing cell culture without any extract was set as the negative control group, a total of 4 groups, each with 6 empty cells. Placed in a cell incubator for culture, on the 1st, 3rd and 7th day, 10 μL CCK-8 solution was added to each well. After 4 hours, the reacted liquid was transferred to a 96-well plate for absorbance test, and the absorbance at a wavelength of 450 nm was read using a marker. The relative proliferation rate (RGR) of rat bone marrow mesenchymal stem cells (BMSCs) in each experimental group was calculated based on the measured absorbance (OD value).

[0035] 2.5 Alkaline phosphatase test The sterilized scaffolds were placed on a 96-well plate, and 100 μL of cell suspension (6×10 5The cell suspension containing BMSCs (100 μg / mL) was placed in a cell incubator for culture. The culture medium was replaced every other day. The wells were taken out on days 7 and 14, the original culture medium was discarded, and PBS was added to gently rinse three times. Then, alkaline phosphatase lysis solution was added. The sample surface was repeatedly blown with a micropipette and placed in a 4°C refrigerator to lyse the cells for 30 min, and the cell lysate was collected. The total protein content of the cells was quantified using the Bradford assay method. The blank control group was a 96-well plate with 50 uL of detection buffer and 50 uL of colorimetric substrate added. The samples were taken out on days 7 and 14, and the absorbance at a wavelength of 504 nm was measured according to the instructions of the alkaline phosphatase kit to detect the activity of alkaline phosphatase, thereby analyzing the bone induction performance of the three groups of polyetheretherketone scaffolds.

[0036] 2.6 Cell mineralization assay Calcium deposition is a specific marker of osteoblast differentiation and is often used to evaluate the osteoinductive potential of artificial bone biomaterials. 5 cm 2 The cells were fixed in the well plate for use. According to the experimental groups, 2 mL of osteogenic induction medium containing the extract prepared from the scaffolds of the polyetheretherketone, sulfonated polyetheretherketone, and sulfonated polyetheretherketone-apatite groups were added and placed in a cell culture incubator for culture. On the 7th and 14th days of incubation in the incubator, the well plate was taken out, the liquid in the well plate was sucked out, and the cells were fully rinsed with PBS solution. After fixation with 4% paraformaldehyde, the cells were stained with alizarin red dye for 5 minutes, the dye was sucked out, and the cells were rinsed with PBS solution. The staining was observed under an electron microscope. The cell mineralization experiment was used to evaluate whether the three groups of polyetheretherketone scaffolds had the ability to induce rat bone marrow mesenchymal stem cells to differentiate into osteoblasts.

[0037] 3 Results 3.1 Preparation and characterization of 3D printed polyetheretherketone scaffolds and their modified scaffolds 3.1.1 Morphological observation The general morphology of the polyetheretherketone scaffold printed by fused deposition 3D printing technology and the scaffold modified by sulfonation and wet chemical methods were captured by a high-definition camera.

[0038] The appearance observation results are as follows Figure 1 , Figure 2 and Figure 3As shown in the figure, the sizes of the three groups of polyetheretherketone scaffolds are all 20mm*20mm*1mm, and it can be seen that the internal pore structure is symmetrical and regular. From a macroscopic perspective, the physical structure of the polyetheretherketone scaffold did not change after the sulfonation and wet chemical treatments, while the color of the sulfonated polyetheretherketone-apatite group treated by sulfonation and wet chemical treatments turned slightly white, which is because the hydroxyapatite-like material adhered to the surface of the polyetheretherketone, thus changing its surface color.

[0039] 3.1.2 Microscopic morphology and structure observation Figures 4 to 12 The results of rolling difference of the microscopic morphology of polyetheretherketone scaffolds using scanning electron microscopy (SEM, JSM-6490LV). All three groups of polyetheretherketone scaffolds have macroscopic pores and a three-dimensional scaffold structure with interconnected pores. The surface of the unmodified scaffold of the unmodified polyetheretherketone group is relatively smooth and flat; the surface of the sulfonated polyetheretherketone scaffold has uneven protrusions and pores of different sizes, ranging from a few microns to hundreds of microns, and the shapes of the pores are irregular; the sulfonated polysulfonated polyetheretherketone-apatite scaffold presents a more complex microstructure, with calcium-phosphorus compounds attached to the surface, and hydroxyapatite-like scaffolds are obviously attached to the surface of the scaffold, indicating that hydroxyapatite-like scaffolds have been successfully attached to the sulfonated polyetheretherketone scaffolds through sulfonation and wet chemical methods.

[0040] 3.1.3 Analysis of element type distribution The element types of the three groups of polyetheretherketone scaffolds were observed and analyzed using an EDS spectrometer (EDS, JSM-6490LV). Fig.13 S, Ca, and P were detected on the surface of the polyetheretherketone scaffold modified by sulfonation and wet chemical methods. Among them, sulfur was generated by the sulfonic functional group generated by polyetheretherketone in the sulfonation reaction, while Ca and P came from the hydroxyapatite produced by the wet chemical method. The calcium-phosphorus molar ratio of hydroxyapatite synthesized by wet chemical method was determined by quantitative analysis of the analyzed elements by EDS. The results are shown in Table 2, indicating that the average calcium-phosphorus ratio decreases with the decrease in the concentration of calcium-phosphorus solution. In addition, the Ca / P ratio of the sample synthesized in 10X solution at 70°C is close to the stoichiometric ratio of HA (1.67). According to current research, the calcium-phosphorus compound under this stoichiometric ratio has the best bone induction. Therefore, the unmodified polyetheretherketone scaffold of the 5X-70C-72H group was used as the sulfonated polysulfonated polyetheretherketone-apatite group scaffold in subsequent studies.

[0041] Table 2 EDS determination of calcium-phosphorus ratio after wet chemical modification

[0042] 3.1.4 Fourier transform infrared spectroscopy analysis Fourier transform infrared spectrometer (FTIR, NICONET Nexus670) was used to analyze the infrared characteristic absorption peaks of the three groups of polyetheretherketone scaffolds: unmodified polyetheretherketone, sulfonated polyetheretherketone, and sulfonated polyetheretherketone-apatite to determine the element types and evaluate whether the modification was successful. The results of Fourier transform infrared spectroscopy analysis are shown in Figure 2. Fig.14 As shown, 1255 cm-1 can be seen in the sulfonated polyetheretherketone and sulfonated polyetheretherketone-apatite groups. -1 and 1050cm -1 The appearance of the sulfonated polyetheretherketone-apatite group, PO 4 3- At 560, 600 and 1100 cm 1- A strong infrared absorption band is formed at the hydroxyapatite-like component, indicating that the hydroxyapatite-like calcium phosphate compound is successfully introduced into the stent by the wet chemical method.

[0043] 3.1.5 Thermogravimetric analysis The thermal properties of three groups of polyetheretherketone scaffolds, namely polyetheretherketone, sulfonated polyetheretherketone, and sulfonated polyetheretherketone-apatite, were characterized and analyzed using a thermogravimetric analyzer (TGA, TA2050). Fig.15 The thermogravimetric curves of the polyetheretherketone group and the sulfonated polyetheretherketone group showed no weight loss at 100-560°C. However, when the temperature reached the range of 560-600°C, the organic polymer materials of the polyetheretherketone and its sulfonated scaffolds underwent thermal degradation, resulting in a gradual weight loss, indicating that the polyetheretherketone modified by the sulfonation method still has thermal stability. The sulfonated polyetheretherketone-apatite group showed a small amount of weight loss in the temperature range of about 200-270°C. This is because the [Ca(HP0 4 ) 3 ] 4 - is decomposed into calcium metaphosphate, which shows that the sulfonated polyetheretherketone-apatite artificial bone tissue prepared by sulfonation and wet chemical methods has thermal stability.

[0044] 3.1.6 Surface roughness analysis The surface roughness of the three groups of artificial bones was analyzed by atomic force microscopy. The results were as follows: Figures 16 to 20As shown in the figure, the microscopic surface of the unmodified polyetheretherketone group scaffold is the smoothest, with a surface roughness (RA) of 0.95±0.4 nm and a root mean square roughness (RMS) of 1.24±0.4 nm. The roughness of the polyetheretherketone scaffold after sulfonation modification increases, with an RA value of 1.20±0.4 nm and an RMS value of 1.43±0.4 nm. The surface roughness of the sulfonated polyetheretherketone-apatite group scaffold modified by sulfonation and wet chemical methods is further improved due to the attachment of hydroxyapatite on the surface, with an RA value of 4.26±0.8 nm and an RMS value of 5.33±0.4 nm. The rough surface is more conducive to the attachment of cells and water, thereby improving the bioactivity and bone inductivity of the material.

[0045] 3.1.7 Porosity analysis The porosity of the three groups of polyetheretherketone scaffolds was tested by the Archimedean drainage method. The results are shown in Table 3. The porosity of the three groups of polyetheretherketone was 70±0.02%, 71±0.01%, and 71±0.01%, respectively, which matched the initial set value. The porosity of the three groups of polyetheretherketone scaffolds was consistent with the parameters set during preparation, and the scaffold porosity was close to the porosity of human bone. Nano measurer software was used to measure the pore size. The pore size of the artificial bone in the unmodified polyetheretherketone group was 801.3±24 μm; the pore size of the artificial bone in the sulfonated polyetheretherketone group was 793.7±31 μm; and the pore size of the artificial bone in the sulfonated polyetheretherketone-apatite group was 825.0±39 μm. There was no statistically significant difference among the three groups (ns).

[0046] Table 3 Pore size of polyetheretherketone stent

[0047] 3.1.8 Hydrophilicity analysis The surface contact angles of three groups of polyetheretherketone scaffolds, namely, unmodified polyetheretherketone, sulfonated polyetheretherketone, and sulfonated polyetheretherketone-apatite, were measured using a water contact angle meter (JC, 2000D3). The hydrophilicity of the scaffolds was analyzed by the static drop method. The results are shown in Table 1. Figure 21 to Figure 23 As shown in the figure, it can be seen that the angle of distilled water on the surface of the unmodified polyetheretherketone group is the largest, with a surface contact angle of 86.34°±1.4°, and the water droplet is hemispherical as a whole. The contact angle of the water droplet formed on the surface of the two modified artificial bones is significantly reduced, and the surface of the polyetheretherketone scaffold after sulfonation, its water contact angle is reduced to 68.46°±1.9°, and the water droplet formed on the surface of the sulfonated polyetheretherketone-apatite group is the flattest, and the distilled water spreads the widest on its surface, with a contact angle of 28.94°±5.2°. Fig.24The contact angle of sulfonated PEEK was significantly different from that of unmodified PEEK (p < 0.05), indicating that sulfonation treatment improved hydrophilicity. The contact angle of sulfonated PEEK-apatite composite material was further reduced, and the difference in contact angle was more significant compared with sulfonated PEEK (p < 0.0001). The results of this study showed that sulfonation modification can significantly improve the surface hydrophilicity of PEEK materials, and sulfonation combined with apatite modification further enhanced this property. Artificial bone materials with better surface hydrophilicity are conducive to protein adsorption and provide a better biological microenvironment for cell adhesion, proliferation and differentiation.

[0048] 3.1.9 Mechanical properties analysis of PEEK scaffold As an implanted biomaterial, it must have sufficient mechanical properties. The mechanical properties of three groups of polyetheretherketone scaffolds were tested using a universal testing machine (Instron 5967). The results are as follows: Fig.25 and Fig.26 As shown in the figure, the compression modulus of the unmodified polyetheretherketone scaffold was 491±30 Mpa, and its compressive strength was 23.68±1.25 Mpa, the compression modulus of the sulfonated polyetheretherketone scaffold was 320±37 Mpa, and its compressive strength was 20.22±0.58 Mpa; and the compression modulus of the sulfonated polyetheretherketone-apatite scaffold was 347±39 Mpa, and its compressive strength was 21.30±0.54 Mpa. The analysis of the data showed that the elastic modulus and compressive strength of the unmodified polyetheretherketone scaffold were higher than those of the modified sulfonated polyetheretherketone and sulfonated polyetheretherketone-apatite groups (P<0.001), that is, although the compressive capacity of the sulfonated polyetheretherketone material scaffold would decrease to a certain extent, it matched the mechanical properties of human cancellous bone. There was no significant difference between the sulfonated polyetheretherketone and sulfonated polyetheretherketone-apatite groups, and the two groups had the same compressive resistance. The results of compressive strength and elastic modulus suggest that the modified sulfonated polyetheretherketone and sulfonated polyetheretherketone-apatite polyetheretherketone scaffolds can be used as alternative implant scaffolds for cancellous bone in clinical applications.

[0049] 3.2 In vitro biological evaluation of modified PEEK scaffolds 3.2.1 Cell morphology observation Adhesion is the first step in the interaction between cells and biomaterial surfaces, which can change the subsequent cell cascade reaction. In this part of the experiment, the morphology of rat bone marrow mesenchymal stem cells (BMSCs) was observed by electron microscopy after one week of culture of the prepared samples, so as to evaluate the biocompatibility of three groups of tissue artificial bones. First, the three groups of polyetheretherketone cubic scaffold samples of unmodified polyetheretherketone, sulfonated polyetheretherketone, and sulfonated polyetheretherketone-apatite with a size of 4×4×1.5 mm were sterilized with ethylene oxide. Figure 27 to Figure 32The electron microscope images of cells placed on three groups of scaffolds on the 7th day of culture. The results show that rat bone marrow mesenchymal stem cells are relatively good on the three groups of scaffold samples. Fig. 27 and Fig.28 ,On the surface of the unmodified polyetheretherketone group scaffold, the number of live rat bone marrow mesenchymal stem cells adhering to the scaffold surface was relatively small; Fig.29 and Fig.30 On the surface of the sulfonated polyetheretherketone scaffold, the number of cells adhering to the scaffold in the polyetheretherketone group was more than that in the unmodified polyetheretherketone group, and the cells adhering to the scaffold in this group had a certain degree of elasticity and a full morphology. Cells were observed to extend and grow into the pores of some scaffolds. On the surface of the sulfonated polyetheretherketone-apatite scaffold, Fig.31 and Fig.32 , the number of living cells was the largest, the extracellular matrix covered the surface of the polyetheretherketone scaffold, and the cell proliferation was significantly higher than that of the other two groups.

[0050] 3.2.2 Cell proliferation assay and cytotoxicity analysis Rat bone marrow mesenchymal stem cells were cultured in the culture medium of three groups of polyetheretherketone scaffold extracts, and some samples were taken out on the first, third and fifth days, and the relative proliferation rate of rat bone marrow mesenchymal stem cells was detected by CCK-8 method. The results of cell proliferation experiment are shown in Fig.33 and 34 As shown in the results, the three groups of polyetheretherketone scaffolds, namely, unmodified polyetheretherketone, sulfonated polyetheretherketone, and sulfonated polyetheretherketone-apatite, all showed good tissue compatibility. Rat bone marrow mesenchymal stem cells cultured in the three groups of samples showed a good cell proliferation response state, and the cell activity in the sulfonated polyetheretherketone-apatite group was the highest (P < 0.05). The experiment showed that the polyetheretherketone scaffold modified by sulfonation and wet chemistry was non-toxic and had good cell compatibility.

[0051] 3.2.3 Alkaline phosphatase assay Alkaline phosphatase is an indicator factor for early osteogenic differentiation. In this experiment, it was used as a tool to evaluate the ability of three groups of polyetheretherketone scaffolds to induce rat bone marrow mesenchymal stem cells (BMSCs) to differentiate into osteoblasts. The expression of alkaline phosphatase was collected after co-culturing rat bone marrow mesenchymal stem cells with three groups of tissue artificial bone samples for 7 and 14 days to analyze the osteoinductive properties of the three groups of polyetheretherketone scaffolds. Fig.35 As shown in the figure, on the seventh day and the fourteenth day, the expression of alkaline phosphatase in the sulfonated polyetheretherketone-apatite group was higher than that in the other two groups, and the expression in the unmodified polyetheretherketone group was the lowest. This may be related to the porous structure of sulfonated polyetheretherketone-apatite with hydroxyapatite attached on its surface, which provides a better environment for bone differentiation. This means that sulfonated polyetheretherketone-apatite has good osteoinductive properties and can promote bone differentiation in the early stage.

[0052] 3.2.4 Cell mineralization experiment The ability of unmodified polyetheretherketone, sulfonated polyetheretherketone and sulfonated polyetheretherketone-apatite scaffold materials to induce BMSCs to differentiate into osteoblasts was evaluated by co-culturing the material extract with osteogenic induction medium. Figure 36-41 As shown) shows, the unmodified polyetheretherketone group ( Fig.36 , 37 ) No obvious calcium nodule deposition was observed on the 7th and 14th days, indicating that its osteogenic induction ability was limited; sulfonated polyetheretherketone group ( Fig.38 , 39 ) Slight calcium nodule deposition was observed on the 7th day, and the staining deepened further on the 14th day, indicating that the sulfonation treatment improved the biological activity of the material, which is speculated to be related to the increase in surface polarity and optimization of pore structure after the introduction of sulfonic acid groups; Sulfonated polyetheretherketone-apatite composite material group ( Fig.40 , 41 ) showed significant calcium nodule deposition on the 7th day, and the staining area was larger and denser on the 14th day, indicating that it has stronger osteogenic induction ability, which is speculated to be related to the fact that apatite can release bioactive calcium and phosphate ions, thereby further promoting bone matrix mineralization. The experimental results showed that compared with unmodified polyetheretherketone, sulfonation treatment significantly enhanced the ability of polyetheretherketone scaffolds to induce BMSCs to differentiate into osteoblasts, and after further compounding with apatite, the osteogenic induction ability of the scaffold was further improved. The introduction of apatite not only provides more mineralized ions, but also optimizes the bioactivity of the scaffold together with sulfonated polyetheretherketone, forming a microenvironment that is conducive to bone cell adhesion, proliferation and differentiation. Therefore, sulfonated polyetheretherketone-apatite composite materials have better osteogenic induction potential and have high application prospects in the field of bone tissue engineering and bone repair materials.

Claims

1. A method for preparing microporous polyetheretherketone biomaterials by 3D metal printing, characterized in that: The following steps are involved: (1) Using 3D Max software, the model is designed as a thin slice, the model file is exported in .STL format, and then imported into Ultimaker Cura software to adjust the parameters and perform slicing operations, set its filling rate and theoretical porosity, and save the sliced ​​model in .GCODE format and export it for later use; (2) Import the saved .GCODE file into the 3D printer to print the PEEK bracket; Import the sliced ​​.GCODE file into the 3D printer; Preset the parameters of the fused deposition modeling (FDM) 3D printer, then insert the polyetheretherketone (PEEK) biomedical-grade printing filament into the printing conveying tube, set the printing parameters, select the preset model file and start printing; wash and dry the printed PEEK scaffold to obtain an unmodified PEEK group; (3) injecting 98% by weight concentrated sulfuric acid into a beaker so that it completely immerses the surface of the unmodified polyetheretherketone to perform a sulfonation reaction; after washing, freeze-drying is performed to obtain a sulfonated polyetheretherketone group; (4) immersing the sulfonated sample in simulated body fluid to form a bioactive apatite layer on the substrate; (5) Then, it is modified by wet chemical method and dried in an oven at 37°C to obtain sulfonated polyetheretherketone-apatite group.

2. The method for preparing microporous polyetheretherketone biomaterial by 3D metal printing according to claim 1, characterized in that: In step (1), the model is a cube of 10×10×10 mm and a sheet of 20×20×1.5 mm.

3. The method for preparing microporous polyetheretherketone biomaterial by 3D metal printing according to claim 1, characterized in that: In step (2), the parameters of the fused deposition modeling (FDM) 3D printer are preset as follows: preheating the base plate of the fused deposition modeling (FDM) 3D printer to 100° C., adaptive printing air pressure, nozzle aperture of 0.4 mm, material diameter of 1.75 mm, layer height of 0.2 mm, wall thickness of 1 mm, and printing speed of 20 mm / s.

4. The method for preparing microporous polyetheretherketone biomaterial by 3D metal printing according to claim 1, characterized in that: In step (2), the printing parameters are set as follows: the base plate is heated to 100°C and the print head temperature is heated to 400°C.

5. The method for preparing microporous polyetheretherketone biomaterial by 3D metal printing according to claim 1, characterized in that: In step (2), the polyetheretherketone stent is cleaned and dried by ultrasonically washing with acetone, ethanol and deionized water for 15 min in sequence, and then drying in an oven at 37°C.

6. The method for preparing microporous polyetheretherketone biomaterial by 3D metal printing according to claim 1, characterized in that: In step (3), the sulfonation reaction conditions are: stirring at 37°C and 250 r / min for 3 min.

7. The method for preparing microporous polyetheretherketone biomaterial by 3D metal printing according to claim 1, characterized in that: In step (3), the specific method of freeze-drying after washing is: rinse repeatedly with deionized water three times, then ultrasonically clean in acetone, ethanol and ultrapure water for 10 minutes to remove residues; and freeze-dry in a vacuum freeze dryer; then, soak the sample in deionized water for 5 minutes, rinse the sample repeatedly with deionized water, then ultrasonically clean in acetone, ethanol and ultrapure water for 10 minutes to remove residues; and freeze-dry in a vacuum freeze dryer.

8. The method for preparing microporous polyetheretherketone biomaterial by 3D metal printing according to claim 1, characterized in that: In step (5), the wet chemical modification conditions are: pH = 7.4, temperature 37°C ~ 70°C, time 1 day ~ 3 days.

Citation Information

Patent Citations

  • Surface bone-like apatite coating for polyether-ether-ketone and preparation method

    CN115612154A

  • Method for biomimetic modification of polyether-ether-ketone surface

    CN116397203A

  • Bone-induced polyaryletherketone interbody fusion cage and preparation method thereof

    CN116785032A